Preliminary results of a "Multi-2D" kinematic analysis of "straight- vs. bent-arm" freestyle swimming, using high-speed videography - Prins, J.; Murata, N. M.; Allen, J. S. III. (Biomechanics and Medicine in Swimming XI, 2010)
Synchronized, high-speed digital cameras were used for underwater videotaping of swimmers, each of whom were required to perform a series of trials with both bent-arm and straight-arm pull patterns. The resulting video footage was digitized and processed using "Multi 2-D" motion capture software. Results demonstrated (1.) The advantages of using high-speed videography for quantifying swimming stroke mechanics. (2) The resulting data provided insight into the relationship between the varying degrees of elbow-bend during the pull cycle, and fluctuations in linear hip and wrist velocities.